L’usage d’outils d’échafaudage numériques : comment et pourquoi - Chantal Tremblay; Bruno Poellhuber; Anastassis Kozanitis (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Complex problem solving (CPS) is one of the 21st century skills frequently listed in competency frameworks, which is the case in those for business learners. However, weaknesses observed in recent management graduates suggest that they do not master CPS process. Although this could be explained by a lack of disciplinary knowledge, it is likely that it is also attributable to underdeveloped metacognitive skills. Thus, it seemed promising to us to design digital scaffoldings (DS) based on the theory of scaffolding, in order to guide the learner in his CPS process on the cognitive and metacognitive levels. This research contributes to the literature on the influence of DS by using a qualitative approach aimed at explaining how and why learners mobilize them. Given that results suggest that these learners have little experience with CPS and that we can qualify them as novices, recommendations for designing DS adapted to their level are proposed to support the development of this skill.